Amplitude modulation of all three velocity components in turbulent boundary layers. (31st March 2014) - Talluru, K. M.; Baidya, R.; Hutchins, N.; Marusic, I.
Abstract: A combination of cross-wire probes with an array of flush-mounted skin-friction sensors are used to study the three-dimensional conditional organisation of large-scale structures in a high-Reynolds-number turbulent boundary layer. Previous studies have documented the amplitude modulation of small-scale motions in response to conditionally averaged large-scale events, but the data are largely restricted to the streamwise component of velocity alone. Here, we report results based on all three components of velocity and find that the small-scale spanwise and wall-normal fluctuations ( v and w ) and the instantaneous Reynolds shear stress ( -uw ) are modulated in a very similar manner to that previously noted for the streamwise fluctuations ( u ). The envelope of the small scale fluctuations for all velocity components is well described by the large-scale component of the u fluctuation. These results also confirm the conditional existence of roll modes associated with the very large-scale or 'superstructure' motions.